“My Bitch Is Empty!” An Overview of the Reasons for Pregnancy Loss in Dogs - George Mantziaras; Maja Zakosek Pipan (Veterinary Sciences)
The purpose of this review is to present reasons for pregnancy loss in dogs. Termination of pregnancy can occur at any stage of gestation, sometimes even before pregnancy is diagnosed. If embryonic death occurs before day 35 of gestation, the embryo is absorbed. Fetal death in the second half of gestation leads to abortion or fetal emphysema, maceration, or mummification. Abnormal embryonic development, competition between placental sites, or genetic abnormalities of the embryo(s) can lead to termination of pregnancy. Maternal factors that alter ovarian function or the environment in the oviducts and uterus, such as cystic endometrial hyperplasia or inflammation, can lead to pregnancy loss. Abnormalities of the placenta, uterine torsion, metrocoele, environmental stress, and malnutrition can have detrimental effects on fetal development. Several drugs or medications can also have embryotoxic/teratogenic effect. Endocrinological disorders such as hypoluteodism, gestational diabetes, and hypothyroidism can be reasons for pregnancy failure. Several bacteria, protozoa, and viruses can cause pregnancy loss in dogs. Etiological diagnoses of pregnancy loss in dogs are challenging as the exact causes are not always obvious; so, a multi-faceted approach is required.